Participation of elderly in social groups: quality of life and functional capacity - Denise Akemi Simões de Oliveira; José Roberto Andrade do Nascimento Júnior; Sônia Maria Marques Gomes Bertolini; Daniel Vicentini de Oliveira (Rev Rene)
Objective: to analyze the differences between quality of life and functional capacity in elderly participants and non-participants of groups with social activities. Methods: cross-sectional and analytical study that evaluated 31 participants of the social group (Group 1) and 31 non-participants (Group 2). The quality of life was evaluate for WHOQOL-Bref and WHOQOL-Old questionnaires and the functional capacity for Katz and Lawton scales. Results: elderly from Groups 1 and 2 showed quality of life scores in WHOQOL-Bref corresponding to 73.20 and 71.40 points. Regarding the WHOQOL-Old, both groups reached equal results (84 points). Regarding functional capacity, most elderly (77.4%) of the Group 2 had partial or total dependence on others to accomplish instrumental activities of daily life. Conclusion: the results indicated that elderly who participate in the social group have better quality of life scores in social and intimate domains.